Optimalisasi Green Human Resource Management Dalam Meningkatkan Kinerja Pengelolaan Bisnis Perhotelan (Sebuah Studi Literature) - Dwi Kusumawati, Fitri; Agung Sulistyo (Jurnal Manajemen DIVERSIFIKASI, 2024)
Tourism plays an essential role in empowering the regional economy. Along with its development, tourism encourages the growth of tourism-supporting industries. The hospitality business is one of the sectors supporting sustainable tourism. However, this sector is a contributor to problems related to environmental waste. This situation confirms that management needs to implement sustainable management through capacity building that cares about the environment. Implementing Green Human Resource Management is one of the efforts that can be made. The Green Human Resource Management strategy is an effort to maximize the potential of human resources. This strategy is interpreted as a step in managing human resources towards a green work climate and competency. This study aims to see the implementation of Green Human Resource Management in supporting improving the quality of hotel business performance. This study used a qualitative research design through a literature review that was selected according to predetermined conditions. The results of this study confirm that the application of Green Human Resource Management can improve the quality of human resources. Several steps that can be used include (1) recruitment and selection, (2) training and empowerment, (3) performance appraisal, and (4) attention and compensation